018 Disease control beyond NEDA: the value of non-clinical measures to determine treatment response to natalizumab. Issue 6 (27th May 2022) - Calabresi, Peter A; Kappos, Ludwig; Giovannoni, Gavin; Plavina, Tatiana; Koulinska, Irene; Edwards, Michael R; Kieseier, Bernd; Moor, Carl de; Fisher, Elizabeth
Abstract : Introduction: No evidence of disease activity (NEDA; no relapses, MRI activity, or Expanded Disability Status Scale worsening) is considered a multiple sclerosis (MS) treatment goal. We assessed the independent contributions of NEDA components, serum neurofilament light (sNfL), brain parenchymal fraction (BPF), and other clinical outcomes in defining disease control with natalizumab. Methods: We used AFFIRM data from 792 patients to assess change (baseline to year [Y] 2) in NEDA com- ponents, worsening of Paced Auditory Serial Addition Test, 9-Hole Peg Test, Timed 25-Foot Walk, change (Y1-Y2) in BPF, and Y2 sNfL levels. Comparisons included odds ratios (ORs) for natalizumab vs placebo and area under the receiver-operating characteristic curve (AUC). Results: No MRI activity (OR=9.3; AUC=0.73; P<0.0001 vs. placebo), no relapses (2.7; 0.62; P<0.0001), and sNfL <8 pg/mL (4.1; 0.67; P<0.0001) had the strongest association with natalizumab. The best-fit multivariate logistic regression model included no MRI activity (OR=7.6; 95% CI=5.0–11.5; P<0.0001), sNfL (3.1; 2.2–4.5; P<0.0001) and no relapses (2.1; 1.5–3.0; P<0.0001). Conclusion: MRI activity, sNfL, and relapses had the strongest natalizumab treatment association over 2 years in AFFIRM. sNfL may be useful in defining disease control with natalizumab. *Additional authors: Richard A. Rudick (Biogen, Cambridge, MA, USA), Al Sandrock (Biogen, Cambridge, MA, USA). Support: Biogen. Disclosures: Included on poster. g.giovannoni@qmul.ac.uk